2020
DOI: 10.1021/acsptsci.0c00001
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Antimicrobial Peptide Tuning Permits Membrane Disruption and Interpeptide Synergy

Abstract: The ribosomally produced antimicrobial peptides of bacteria (bacteriocins) represent an unexplored source of membrane-active antibiotics. We designed a library of linear peptides from a circular bacteriocin and show that pore-formation dynamics in bacterial membranes are tunable via selective amino acid substitution. We observed antibacterial interpeptide synergy indicating that fundamentally altering interactions with the membrane enables synergy. Our findings suggest an approach for engineering pore-formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…The peptide was suspended in PBS and added to diluted bacterial cells. GFP-expressing E. coli in the presence of peptide were imaged on the Eclipse Ti-E inverted microscope (Nikon) using GFP and DIC channels for 8 h at 37 • C, with images taken every 10 min (Fields et al, 2020). Syn-xiamencin-2, a peptide with no detectable antimicrobial activity below 128 µM was also evaluated as a negative peptide candidate control.…”
Section: Fluorescence Microscopy and Fluorescence-activated Cell Sortingmentioning
confidence: 99%
See 1 more Smart Citation
“…The peptide was suspended in PBS and added to diluted bacterial cells. GFP-expressing E. coli in the presence of peptide were imaged on the Eclipse Ti-E inverted microscope (Nikon) using GFP and DIC channels for 8 h at 37 • C, with images taken every 10 min (Fields et al, 2020). Syn-xiamencin-2, a peptide with no detectable antimicrobial activity below 128 µM was also evaluated as a negative peptide candidate control.…”
Section: Fluorescence Microscopy and Fluorescence-activated Cell Sortingmentioning
confidence: 99%
“…Since linearized forms containing this region have been shown to be active and capable of optimization, we hypothesized that homologous regions in similar enterocin AS-48-like natural sequences could also serve as a scaffold for peptide sequence optimization. We utilized the truncated 25 amino acid sequence from the active domain of enterocin AS-48 to bioinformatically search for other AS-48 like homologs having high conservation in this active domain, as was previously done to identify safencin AS-48 (Fields et al, 2018(Fields et al, , 2020. Three additional species were identified with highly conserved AS-48-like domain regions, namely, C. sordellii, P. larvae, and B. xiamenensis ( Supplementary Table S1).…”
Section: Peptide Library Designmentioning
confidence: 99%
“…Beyond the novelty to address AMPs’ bioactivity by flow cytometry and using a PSA-virulence analysis (HR) against Psa, this study evaluates the efficiency of each AMP on an assortment of field-collected Psa isolates, and against the Psa reference strain CFBP7286. Additionally, we assayed mixtures of BP100, CA-M, and 3.1, aiming to further elucidate the recent findings pointing towards a synergistic effect of AMPs, particularly if presenting different mechanisms of action, which might increase their potential application in a real case [ 54 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the different roles and efficiency revealed by these AMPs against Psa, the possibility of a synergic effect on bactericidal performance is apparent. The synergic effect of different AMPs has been described as a promising strategy to control pathogenic bacteria [ 71 , 72 , 73 ]. Topman et al [ 54 ] demonstrated that mixtures of AMPs (FK-20 and FdK-20) improved the bacteriostatic and bactericidal effects, reducing in vitro the growth of Xanthomonas sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation